ANALISIS PENGARUH MANAJEMEN KARIR ORGANISASIONAL, KARIR INDIVIDU DAN KOMPETENSI TERHADAP EFEKTIVITAS KARIR KARYAWAN PADA PT BANK RAKYAT INDONESIA (PERSERO) CABANG PEMALANG PROPINSI JAWA TENGAH - Rahayuningsih, Sri (Proceeding SENDI_U, 2015)
The objective of this research is to find out the effect of organizational career managementinfluence, individual career management and competency on the employees career effectivenessof PT. Bank Rakyat Indonesia (Persero) Cabang Pemalang. Primary data concerning oforganizational career management, individual career management, competency and employeescareer effectiveness are being used to conduct this research. The sample of this research were 72employees of variety of PT. Bank Rakyat Indonesia (Persero) Cab.Pemalang organization. Dataanalysis in this research use the multiple linear regression analyses by using SPSSsoftware.According to these data analyses, find out that organizational career managementshould be positively and significantly effect on employees career effectiveness. Individual careermanagement by partially should be positively and significantly effect on employees careereffectiveness. Competency should be positively and significantly effect on employees careereffectiveness. Finally, is that employees career effectiveness level will be greater whencompetency, the Individual career management and organizational career management level arebeing greater.Keyword : Organizational career management, Individual career management, Competency,Employees career effectiveness